Kalibrasi 161 Jam Masjid di Kabupaten Rejang Lebong - Ridhokimura Soderi; Angga Ade Putra; Bintang M. Hakim; Imratul Nabila, Inka; Yuriza Mei Raseli (CV. Doki Course and Training, 2024)
Clock calibration refers to the process of adjusting or resetting a clock or time device to conform to a predetermined time standard. This is done to ensure that the watch or device shows the time accurately and in accordance with applicable standards. The clock calibration process involves resetting the clock in mosques in Rejang Lebong district. This community service aims to increase the accuracy of the mosque's